Reflections on equality, justice and allocation of resources in health: The bioethical point of view to the inequitable society's dilemmas - Evelise Ribeiro Gonçalves; Gelson Luiz de Albuquerque; Alacoque Lorenzini Erdmann; Flavia Souza Ramos; Felipa Rafaela Amadigi (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
Abstract: This article brings a reflection about the dilemma of the allocation of resources to health in a society, as the Brazilian one, marked by severe social inequalities among its citizens. For that, the concepts of equality and justice proposed by Amartya Sen (2001) are discussed and the bioethical point of view is proposed for the searching of an equitable sanitary justice. The conclusion is that this search demands a hard fight which must embrace a thoughtful process towards the construction of public health policies compromised with the interests of the social excluded and seeking for national policies which guarantee the efficacy of the health systems.